2019
DOI: 10.1016/j.molmet.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

GDF15 acts synergistically with liraglutide but is not necessary for the weight loss induced by bariatric surgery in mice

Abstract: Objective Analogues of GDF15 (Growth Differentiation Factor 15) are promising new anti-obesity therapies as pharmacological treatment with GDF15 results in dramatic reductions of food intake and body weight. GDF15 exerts its central anorexic effects by binding to the GFRAL receptor exclusively expressed in the Area Postrema (AP) and the Nucleus of the Solitary Tract (NTS) of the hindbrain. We sought to determine if GDF15 is an indispensable factor for other interventions that cause weight loss and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 19 publications
2
54
1
Order By: Relevance
“…No increase in c-Fos in the DMV and AP occurred after both GDF15 doses in the shrew. GDF15-induced c-Fos distribution within the dorsal vagal complex in the shrew appears to only partially overlap with observations of GDF15-induced c-Fos in mice (Frikke-Schmidt et al, 2019;Tsai et al, 2014). It is difficult to draw direct comparisons across species with only intuitive assumptions of GFRAL expression or distribution within the shew hindbrain; however, our data in the vomiting shrew may suggest GFRAL to be differentially distributed within the hindbrain in a species-specific manner.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…No increase in c-Fos in the DMV and AP occurred after both GDF15 doses in the shrew. GDF15-induced c-Fos distribution within the dorsal vagal complex in the shrew appears to only partially overlap with observations of GDF15-induced c-Fos in mice (Frikke-Schmidt et al, 2019;Tsai et al, 2014). It is difficult to draw direct comparisons across species with only intuitive assumptions of GFRAL expression or distribution within the shew hindbrain; however, our data in the vomiting shrew may suggest GFRAL to be differentially distributed within the hindbrain in a species-specific manner.…”
Section: Discussioncontrasting
confidence: 60%
“…GDF15 signaling has gained significant attention with the nearly simultaneous recent reporting of the identification and characterization of the GFRAL-RET (GDNF family receptor α-like) receptor complex as the cellular target for GDF15-mediated signaling (Emmerson et al, 2017;Hsu et al, 2017;Mullican et al, 2017;Yang et al, 2017). Since this cluster of findings, numerous reports and reviews have demonstrated promise for GDF15-GFRAL signaling in obesity treatment (Frikke-Schmidt et al, 2019;Patel et al, 2019;Tsai et al, 2018). Recently published data (Hsu et al, 2017) have suggested that GFRAL knockout (KO) mice were insensitive to long-term anorexia and weight loss produced by the highly emetogenic and widely prescribed chemotherapy agent cisplatin (Herrstedt, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The GDF15 receptor, GFRAL (GDNF-family receptor α-like) is located exclusively in a small population of cells in the in the area postrema (AP) and nucleus of the tractus solitarius (NTS) of the mouse dorsomedial medulla oblongata, ( Mullican et al, 2017 ; Yang et al, 2017 ; Emmerson et al, 2017 ; Hsu et al, 2017 ) a brainstem region containing a number of characterised neurons that previously have been linked with appetite regulation ( Luckman, 1992 ; Rinaman et al, 1993 ; Larsen et al, 1997 ; Lawrence et al, 2000 ; Luckman and Lawrence, 2003 ; Ellacott et al, 2006 ; D'Agostino et al, 2016 ; Roman et al, 2016 ; Frikke-Schmidt et al, 2019 ). Administration of recombinant GDF15 reduces food intake, but not in GFRAL knock-out mice ( Mullican et al, 2017 ; Yang et al, 2017 ; Emmerson et al, 2017 ; Hsu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in fasting and post-prandial FGF-21 was observed in adolescents up to three months post SG 26 . Additionally, FGF-21 was found to correlate with weight loss in adolescents following SG 27 . We wonder if the lack of an increase in FGF-21 in SG in our study was due to the age of the mice, or whether we missed an early increase in FGF-21 by only testing plasma samples from 2 months after SG.…”
Section: Discussionmentioning
confidence: 91%